Foreign practice of using an escrow account contract. Experience of the USA and the UK - Pylypenko, Pylyp; Synchuk , Svitlana (Actual problems of law (Aktual'ni problemi pravoznavstva), 2024)
The article deals with the positions of the US and UK courts regarding the nature of the escrow account contract, the rights and obligations of the subjects of this legal relationship. It is established that in American law, an escrow contract is a tripartite obligation between the depositor, the escrow agent and the beneficiary. It is argued that at the first stage of the legal relationship existence, the escrow agent performs the functions of an agent at the same time for the depositor and the beneficiary, and also performs a role close to the role of a trustee (with a certain difference). At the second stage of the legal relationship existence, the escrow agent performs only the second part of the functions, namely the role that is as close as possible to the trustee. It is substantiated that in US law, the escrow account agreement refers to accessory obligations. The peculiarities of the relation back doctrine application by American courts were dealt with. It is established by the author that it is necessary to sign the contract between the parties in the form of a written document and to perform the actual transfer of property by the depositor to the escrow agent in order for an escrow account contract in the USA to be concluded. The aforementioned gives grounds to consider this contract to be real. It is noted that in most states, escrow agents can only be legal entities that have received a special escrow license or a license to carry out money transfers, and the main provisions regarding the limits of escrow agent liability in the USA have also been dealt with. The understanding of the concept of escrow agent and escrow trustee in the legal doctrine and judicial practice of Great Britain is compared. The fiduciary duties of an escrow agent in the UK are dealt with. The ways of solving the problem of legal regime of property in escrow by the UK courts are outlined.